Hubungan Antara Pengetahuan Ibu Tentang Kanker Payudara Dengan Perilaku Sadari Pada Kader Posyandu Kecamatan Delanggu - Satriya Pamungkas, Kakung, dr. Yusuf Alam Romadhon, M.Kes, dr. Endang Widhiyastuti (2015)
Background: Cancer is a disease with a high pravelence in the world. Top five cancers in the world is lung cancer, breast cancer, colon cancer, gastric cancer, and liver cancer. Survey WHO states that 8-9 percent of women with breast cancer. Indonesia in 2007 breast cancer ranks first in-patients by 16,85% and 21,69% of outpatients. One of the high incidence of breast cancer is less education as a teenager in detecting and dealing with early breast cancer. Objective: This study has the objective to determine whether or not the relationship between knowledge about breast cancer and BSE on Posyandu cadre district of Delanggu. Methods: This study used an analytical study design with cross sectional approach. The sampling technique purposive sampling. Results: There were 37 respondents. Data analysis used Somers'd. The results of this study showed a p